Inequalities within Uniting Reformed Church in Southern Africa on gender, with special reference to lGBTQIA+: Imago Dei - L. Modise (Acta Theologica)
This article consists of five parts on equality within faith communities. First, the focus is on the creation of human beings as the image of God on an equal basis. The premise is that LGBTQIA+ people are created as human beings in the image of God, deserving to be welcomed in faith communities. Second, the article focuses on the way in which missionaries have taught African converts to interpret the Bible on many serious human rights issues. Third, the position of the Uniting Reformed Church in Southern Africa (URCSA) is discussed, utilising the contents of the General Synods, spanning from Pietermaritzburg (2005) to Stellenbosch (2022). Fourth, this study reflects on the challenges faced by denominations who accept LGBTQIA+ people regarding marriage and their ordination. The challenge seems to be about the fundamental reading of the Bible, confession, and Church Order articles, which are discussed here. Fifth, recommendations are proposed to address this inequality. This article is approached from an anthropological-missional viewpoint when addressing this inequality within communities of faith.